Development of a Positive Conformity-Based Domino Card Media to Enhance Senior High School Students’ Learning Motivation - Saputri, Intan Wahyu; Cahyaningrum, Vesti Dwi; Efendi, Moh. Yusuf (KONSELI: Jurnal Bimbingan dan Konseling (E-Journal), 2026)
Learning motivation is an important factor in determining the success of the learning process. However, various challenges have led to a decline in learning motivation, which in turn affectsthe quality of learning, especially at the senior high school level. A report indicates that Indonesia is experiencing learning loss, characterized by a decline in students' learning motivation and academic achievement. Interviews conducted at SMAN 1 Kepohbaru revealed that students' learning motivation is not yet optimal, as reflected in a lack of responsibility for learning, limited readiness to learn, and enthusiasm for learning that is influenced by peers. Guidance and counselling services still focus on individual counselling and have not yet utilized learning media as a means of delivering services. This study aims to develop domino cards as a medium to enhance students' learning motivation through positive peer conformity, as well as to assess the feasibility of domino cards in optimizing students' learning motivation in guidance and counselling services. This study applies a Research and Development (R&D) approach adapted from the Borg and Gall model. The subjects of this study were 60 eleventh- grade students at SMAN 1 Kepohbaru. The results indicate that the developed media obtained a feasibility score of 93.36% which falls into the “very good” category, indicating that it is appropriate for use in guidance and counselling services.